INTEGRITAS KLIEN, PENILAIAN RISIKO AUDIT DAN KEABSAHAN BUKTI AUDIT - Agus, Andi (JURNAL FAIRNESS, 2015)
The purpose of this study is to examine the influence of client integrity and audit risk assessment toward audit evidence validity by exploring Integrity Theory, Risk Theory, and Evedence Theory. The data used in this study are primary data by collecting data through questionnaires. A total of 80 auditors (respondents) who works in the Office of Audit Board of Indonesia Representative of South Sulawesi were selected as a sample of this study. This study found that client's integrity positively influence validity audit evidence. It indicates that the higher integrity lead to higher validity audit evidence. In contrast, audit risk assessment does not influence validity audit evidence. It indicates that the higher audit risk assessment does not lead to higher influence validity audit evidence. This study also found that client's integrity and audit risk assessment together can increase the validity of audit evidence